Equivalent air change rate by upper room UVGI system - Bang, Jongil; Sung, Minki; Kim, Sunsook; Kato, Shunsuke (15th Conference of the International Society of Indoor Air Quality and Climate, INDOOR AIR 2018, 2018)
UR-UVGI (Upper Room Ultraviolet Germicidal Irradiation) systems can be used as an additional countermeasure of ventilation systems against airborne infectious diseases in healthcare-related buildings. In this study, an UR-UVGI system was evaluated using a novel CFD simulation method in a model room used in an experimental case. The results for several cases showed inactivation rate of 98.3 ~ 96.2% for airborne vaccinia virus in the steady state condition. Equivalent air change per hour (EACH) of the UR-UVGI system was 4.5 ~ 16.5 ACH in the decay condition. Heat boxes accelerated the inactivation of airborne virus by UR-UVGI. However, the discrepancy between simulation and experiment results was observed probably because of lack of the detailed experimental conditions.
Keywords: Air change rates; Airborne virus; CFD simulations; Experimental conditions; Infectious disease; Steady-state condition; Ultraviolet germicidal irradiations; Ventilation systems; ACH; Airborne infection; CFD; UVGI